A Study of the Results of Time-Dependent Ginzburg-Landau Equation Using Scilab - Tanzillal Alfargana; Artono Dwijo Sutomo; Fuad Anwar (Universitas Sebelas Maret, 2024)
This study aims to examine computational (numerical) programs in solving the Ginzburg-Landau Time-Dependent Equation. The Ginzburg-Landau Time-Dependent Equation (TDGL), which is often used to model the dynamics of superconductors in external magnetic fields. The TDGL equation is made using the Scilab platform, then the results are compared with the results of Fortran. This study involves experiments with variations in superconductor size to observe their effect on simulation results. The main focus of this study is to study the relationship between the mean magnetization of superconductors and external magnetic fields (He), as well as to evaluate the accuracy and efficiency of the results obtained from the two computing platforms. These results show the relationship between the mean of the superconductor magnetization and the external magnetic field, as well as a comparison of the Vs He graph of Scilab and Fortran showing the relationship between the superconductor order parameters and the external magnetic field.